Execution of Computerized Management Systems in Facility Maintenance Services of Government Hospitals - Mydin, Md Azree Othuman; Azahar, Noor Farisya; Sani, Norazmawati Md; Abas, Noor Faisal (EDP Sciences, 2014)
Maintenance management of a hospital is the most important element in determining the ability of a hospital to provide its services successfully. On 28th October 1996, the Ministry of Health (MOH) privatized five Hospital Support Services (HSS), one of them being Facility and Engineering Maintenance Services (FEMS). Currently, the Ministry has granted concessions for the privatized services to three contractors where they have established and are maintaining their own basic Management Information System (MIS) to manage the entire project and track the work performed for all of their services. These MISs consist of a variety of modules which help maintenance strategies adopted in a building run smoothly. The purpose of this paper is to study the utilization of computerized management system modules in the MISs of those three HSS providers and to investigate problems that have occurred during the utilization of these systems. This study was conducted in the form of case studies at three different hospitals that subscribed to three different concession companies. Targeting maintenance staff and users of computerized management systems, 60 sets of questionnaires were distributed and interview sessions were conducted. This study will also highlight the challenges of using computerized management systems and propose suitable recommendations to improve the utilization of such systems.